Application of Thermal Analysis to Evaluate Pharmaceutical Preparations Containing Theophylline - Paweł Ramos (MDPI AG, 2022)
Confirmation of the composition of pharmaceutical products is an essential pharmaceutical issue. The purity and identity of active pharmaceutical ingredients (API) in the finished drug impact the effect of correct and safe pharmacotherapy. The currently frequently used advanced analytical methods are laborious and time-consuming. On the other hand, less advanced techniques such as UV-Vis spectrophotometry are less specific. In the presented study, thermogravimetry analysis (TGA)-supported by calculated differential thermal analysis (c-DTA)-was proposed to evaluate the composition of pharmaceutical preparations containing theophylline and aminophylline. Due to its advantages, the TGA method can be an alternative used for screening assessment of the composition of pharmaceutical preparations. The obtained results show that TGA supported by c-DTA is a suitable screening method for assessing the composition of pharmaceutical preparations containing theophylline and aminophylline. Both thermal techniques complement each other to obtain reliable results. In contrast to the pharmacopoeial UV-Vis method, TGA allows for unambiguous identification and distinction of one- and two-component pharmaceutical preparations. Moreover, thanks to TGA and c-DTA, it was possible to identify the excipient used in the formulation of a commercial drug and to detect considerable amounts of lactose in the experimentally prepared counterfeit formulation. The research herein indicates the multifaceted application and usefulness of TGA and c-DTA in pharmacology.